2003
DOI: 10.1177/15648265030244s109
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Trials of a Micronutrient Dietary Supplement in Schoolchildren and Pregnant Women in Tanzania

Abstract: Traditionally, the main strategies used to control micronutrient deficiencies have been food diversification, consumption of medicinal supplements, and food fortification. In Tanzania, we conducted efficacy trials using a dietary supplement as a fourth approach. These were randomized, double-blind, placebo-controlled efficacy trials conducted separately first in children and later in pregnant women. The dietary supplement was a powder used to prepare an orange-flavored beverage. In the school trial, children c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This was not the case in the present study, where the consumption of vegetables was low and monotonous, helping to explain the low micronutrient and fibre intakes found among the adolescents. Given the low intake of certain nutrients, there has been a suggestion that the use of dietary supplements should be widely encouraged among children and adolescents ( 30 , 31 ) . Other strategies have been developed to provide adequate nutrient intakes.…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case in the present study, where the consumption of vegetables was low and monotonous, helping to explain the low micronutrient and fibre intakes found among the adolescents. Given the low intake of certain nutrients, there has been a suggestion that the use of dietary supplements should be widely encouraged among children and adolescents ( 30 , 31 ) . Other strategies have been developed to provide adequate nutrient intakes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of anthropometry, there were no significant differences in mean weight, height, and BMI between groups at the baseline examination [7]. However, at follow-up, incremental changes in weight (1.79 versus 1.24 kg, a difference of 0.55 kg); in height (3.2 cm versus 2.6 cm, a difference of 0.6 cm); and in BMI units (0.88 versus 0.53, a difference of 0.35) were significantly higher in the fortified compared with the nonfortified group (results not shown).…”
Section: Anthropometric-measurement Changesmentioning
confidence: 77%
“…In the Dodoma Region of Tanzania, two separate double-blind, placebo-controlled field efficacy trials have been completed using a multiple-micronutrientfortified dietary supplement. The first trial [6,7] was conducted with young primary schoolchildren and the second with pregnant women, some of whom were followed postpartum during 4 weeks of lactation [8].…”
Section: Trials Of a Micronutrient Dietary Supplement In Tanzaniamentioning
confidence: 99%
“…In older children, there is also evidence of improved outcomes related to supplementation. A supplementation study in Tanzania showed anthropometric improvements and improvements in iron and vitamin A status among primary-school children consuming fortified beverages (Ash et al 2003;Latham et al 2003). And in Cambodia, iron and folic acid supplementation was shown to decrease the prevalence of anemia among 5-to 11-year-olds, but was less effective among 12-to 15-year-olds (Longfils et al 2005).…”
Section: Other Health and Nutrition Interventionsmentioning
confidence: 99%
“…Several other studies also evaluate the effectiveness of supplements on micronutrient status among school-aged children. See, for exampleLatham et al (2003) andSolon et al (2003).…”
mentioning
confidence: 99%